Optimalkan potensi mahasiswa: Program pelatihan kewirausahaan terintegrasi - Karma; Seniorita; Andi Baso Adil Natsir; Muhammad Ridwan; Mauli Kasmi (Jurnal Dedikasi Masyarakat, 2021)
Entrepreneurship development among students has an important role in increasing creativity, innovation, and economic independence. The background to the importance of entrepreneurship for students is highlighted as a response to challenges in an increasingly competitive world of work and the increasing need for economic independence. The structured implementation method is described, including tenant recruitment patterns, approaches to selecting prospective participants, as well as the entrepreneurship training methods applied. The results of entrepreneurship development activities include the formation of selected student business groups (tenants), the implementation of entrepreneurship training, and a positive impact on students' mindsets and abilities in generating business. In its implementation, various effective strategies have been implemented to overcome obstacles such as limited resources, differences in background and knowledge, as well as technical and technological obstacles. Entrepreneurship development activities have succeeded in making a significant contribution to shaping the entrepreneurial spirit and economic independence of students. Even though faced with various obstacles, appropriate mitigation efforts have produced positive impacts that can be seen from the formation of student business groups, changes in mindset, and increased students' ability to generate business. The next steps need to focus on strengthening and expanding the program to broaden its positive impact and maintain the sustainability of student entrepreneurial initiatives.